2019
DOI: 10.1177/0145482x19845756
|View full text |Cite
|
Sign up to set email alerts
|

Determining Type and Amount of Service Delivery Time by Teachers of Students with Visual Impairments: Results of a National Validation Study of the VISSIT

Abstract: Introduction: This research followed the lead of an initial validation study and responded to the call from the state education agency–endorsed Service Intensity Subcommittee of the Texas Action Committee for the Education of Students with Visual Impairments to conduct a larger scale validation study on the Visual Impairment Scale of Service Intensity of Texas (VISSIT). Methods: The authors collected survey data from 77 respondents using a mixed-methods survey research design. These data were used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…They also reported it was better to use this tool when determining service type and amount of service time because it is more objective and based in research. These findings showed close similarities with the results of initial and national validation studies on the VISSIT (Pogrund et al, 2015; 2019). For instance, in both studies, the vast majority of the participants were willing to use the VISSIT again for service intensity determination purpose in the future, 96% and 93%, respectively.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…They also reported it was better to use this tool when determining service type and amount of service time because it is more objective and based in research. These findings showed close similarities with the results of initial and national validation studies on the VISSIT (Pogrund et al, 2015; 2019). For instance, in both studies, the vast majority of the participants were willing to use the VISSIT again for service intensity determination purpose in the future, 96% and 93%, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…In the initial validation study (Pogrund et al, 2015), validation and reliability of the VISSIT were examined, and the instrument was found to be a moderately valid and reliable. A large-scale national validation study on the VISSIT (Pogrund et al, 2019) showed high validity and reliability and supported social, consequential, content, and construct validity.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…When these children reach transition age, they may face challenges, including the need for accommodations (Sanford et al, 2011), self-advocacy skills (Brinkerhoff, McGuire, & Shaw, 2002), and specialized programs (Tagayuna, Stodden, Chang, Zeleznik, & Whelley, 2005). These areas are folded into the ECC (Hatlen, 1996;Huebner, Merk-Adam, Stryker, & Wolffe, 2004), a set of best practices for working with youths with visual impairments to be incorporated into service delivery planning (Pogrund, Darst, & Munro, 2019), yet often add to the educator's workload (Opie, 2018). However, multiple organizations collaborating to deliver transition services in this program have made a positive impact (Brown, Brown, & Glaser, 2013;Coduti et al, 2017), and research has shown that by highlighting the ECC during instruction, students were better able to attain goals of postsecondary educational success and job employment (Wolffe & Kelly, 2011;Crudden, 2012).…”
Section: Introductionmentioning
confidence: 99%